Journals of Expeditions of Discovery into Central Australia and Overland from Adelaide to King George's Sound in the Years 1840-1: Sent By the Colonists of South Australia, with the Sanction and Support of the Government: Including an Account of the Manners and Customs of the Aborigines and the State of Their Relations with Europeans $1 (BVolume 02s - Eyre, Edward John, 1815-1901 (Salt Lake City, UT : Project Gutenberg, 2004)
"Journals of Expeditions of Discovery into Central Australia and Overland from Adelaide to King George's Sound in the Years 1840-1" by Edward John Eyre is a historical account written during the mid-19th century. The book chronicles Eyre's challenging and perilous explorations of Australia's interior, providing insights into his encounters with the indigenous populations, the landscape, and the hardships faced during the journey. At the start of the narrative, Eyre reflects on the tragic death of his overseer, which marks a critical juncture in their expedition. He describes a harrowing scene where bandits have plundered their camp, leaving him in the Australian desert with a single, untrustworthy native companion. Eyre grapples with feelings of isolation and vulnerability as he realizes he must navigate the harsh landscape alone, struggling to maintain his resolve. He provides detailed accounts of their food shortages, encounters with hostile natives, and the fluctuating state of his supplies as they trek towards King George's Sound, thereby setting the tone for the treacherous journey ahead. (This is an automatically generated summary.)
Release date is 2004-10-05
Produced by Col Choat
Keywords: Australia -- Discovery and exploration; Ethnology -- Australia